The Influence of Stad, NHT and Conventional Cooperative Models and the Ability to Read the Qur'an on Fiqh Learning Outcomes - Muhammad Ridho Abdul Rozaq; Wati Susilawati; Adam Malik (al-Afkar, Journal For Islamic Studies, 2025)
This study aims to analyze the effect of the implementation of learning models (STAD, NHT and Conventional) and BTQ ability on Fiqh learning outcomes. This research method uses an experimental method with a quasi-experimental design. The population of this study was 60 students of grade 4 of SDIT Plus Al-Muhsinin. The instruments used consisted of; 1) Tests given to students totaling 20 multiple-choice questions; 2) Al-Qur'an reading ability test through oral tests, namely reading and writing the Al-Qur'an. The data analysis technique used in this study used two-way ANOVA analysis. The results of this study indicate that; 1) there is no difference in Students' Fiqh Learning Outcomes based on learning models (STAD, NHT, and Conventional), 2) there is a difference in Students' Fiqh Learning Outcomes based on BTQ ability, 3) there is no interaction between learning models and BTQ ability in determining students' Fiqh learning outcomes. Thus, learning outcomes are not influenced by the implementation of learning models but are influenced by the ability to read and write the Al-Qur'an.